2023
DOI: 10.1093/plphys/kiad236
|View full text |Cite
|
Sign up to set email alerts
|

Novel players in organogenesis and flavonoid biosynthesis in cucumber glandular trichomes

Abstract: Glandular trichomes (GTs) are outgrowths of plant epidermal cells that secrete and store specialized secondary metabolites that protect plants against biotic and abiotic stresses and have economic importance for human use. While extensive work has been done to understand the molecular mechanisms of trichome organogenesis in Arabidopsis (Arabidopsis thaliana), which forms unicellular, non-glandular trichomes (NGTs), little is known about the mechanisms of GT development or regulation of secondary metabolites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Researchers note that the dense trichomes on the leaves and stems of plants not only help them adapt to arid environments but also contribute to their defense against extreme temperatures and ultraviolet radiation. Additionally, these trichomes potentially serve as physical barriers against pests and pathogens [89,90]. Specifically, our current study has shown that the formation of trichomes is significantly increased in A. nanus plants subjected to salt stress (Unpublished data).…”
Section: Synergistic Effects Of Multiple Environmental Pressuresmentioning
confidence: 60%
“…Researchers note that the dense trichomes on the leaves and stems of plants not only help them adapt to arid environments but also contribute to their defense against extreme temperatures and ultraviolet radiation. Additionally, these trichomes potentially serve as physical barriers against pests and pathogens [89,90]. Specifically, our current study has shown that the formation of trichomes is significantly increased in A. nanus plants subjected to salt stress (Unpublished data).…”
Section: Synergistic Effects Of Multiple Environmental Pressuresmentioning
confidence: 60%
“…The rapid expansion of the CER1 family in the Chinese chestnut is related not only to the thickening of the wax layer to adapt to the arid environment in northern China, but possibly also to the development of chestnut glandular trichomes [ 58 ]. In cucumbers, CER1 can promote the formation of glandular trichomes [ 36 ]. Although we cannot confirm whether Chinese chestnut CER1 is also required in the glandular trichome development in addition to wax layer synthesis, it is highly likely that Chinese chestnut has adapted to cold and dry environments by promoting the development of leaf appendages through the expansion of the CER1 family.…”
Section: Discussionmentioning
confidence: 99%
“…Terpenoids are derived from one of two biosynthetic pathways: the mevalonic acid (MVA) and plastidial 2-C-methylerythritol 4-phosphate (MEP) pathways. Flavonoid and terpenoid metabolism have been studied in many species, including Cucumis sativus [4], Passiflora edulis [5], Cryptomeria fortunei [6], and Primula veris [7]. Metabolomic analysis targeting terpenoids has led to the identification of 50 terpenoid metabolites, including 27 triterpenoid saponins and 11 triterpenes [8].…”
Section: Introductionmentioning
confidence: 99%